An efficient crowbar to improve the low voltage ride-through capability of wind turbines based on DFIG excited by an indirect matrix converter. (10th February 2020) - Khajeh, Ahmad; Ghazi, Reza; Abardeh, Mohamad Hosseini; Sadegh, Mahmoud Oukati
Due to numerous advantages, in this work, the traditional back-to-back converter is substituted with an indirect matrix converter (IMC) to control the doubly-fed induction generator (DFIG). The recent grid codes require that the wind turbines must have the low voltage ride-through (LVRT) capability. One of the main challenges of the IMC that slows down the industrial applications is the fault currents handling. In this paper, a new low cost, simple and reliable method is proposed to protect the IMC from large fault currents. This method is based on a novel crowbar structure. The PSIM simulation results confirm the efficiency of the proposed method in satisfying the new LVRT standards. Also, experimental results of a laboratory prototype verify the effectiveness of the proposed method.